Ground for new thoughts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Dynamics and Diversity. Soil Fertility and Farming. Livelihoods in Africa Edited by I Scoones, Earthscan - International Institute for Environment and Development (IIED) and Institute of Development Studies, Sussex (IDS). 2001. 244 pp. ISBN 1 85383 820